Biomechanical and biological features of hyaluronic acid in combination with chondroitin and platelet rich plasma for regenerative medicine applications - Vassallo, Valentina; Di Meo, Celeste; D’Agostino, Antonella; La Gatta, Annalisa; Cimini, Donatella; Toro, Giuseppe; Iolascon, Giovanni; Mastrogiacomo, Maddalena; Schiraldi, Chiara (Frontiers in Bioengineering and Biotechnology, 2025)
Currently, one of the most common treatments for osteoarthritis (OA) is viscosupplementation using intra-articular injectable gels, often based on glycosaminoglycans (GAGs), specifically hyaluronic acid (HA) and, in some cases, chondroitin sulfate (CS). Recently, the potential benefits of pharma-grade biofermentative unsulfated chondroitin (BC) have been established, particularly when combined with high molecular weight hyaluronan (HHA). Beyond GAGs, platelet-rich plasma (PRP) has also been reported to have beneficial effects, although many clinical studies lack proper control groups. The aim of this study was to perform a comparative analysis of injectable formulations based on BC combined with HHA (HHA/BC), both alone and in combination with PRP, to evaluate their rheological and biological properties. Flow curves and mechanical spectra of HHA/BC and HHA/BC+PRP were obtained to assess their viscoelastic behavior in relation to synovial fluid characteristics. Then, these two formulations were tested on human chondrocytes isolated from OA joints to investigate their functional role in vitro on specific biochemical pathways. Additionally, a chondrocyte monolayer scratch assay was performed to evaluate their repair potential using time-lapse video-microscopy. Finally, chondrocytes were cultured in GAG-based gels on transwell inserts for 14 days to mimic a 3D-like in vitro environment. HHA/BC+PRP exhibited a consistent rheological profile, supporting its potential application in intra-articular injections. Furthermore, the maintenance of cell phenotype was confirmed through the analysis of collagen type 2A1 (COL2A1) and aggrecan (ACAN) expression. The addition of PRP further enhanced the ability of GAGs to reduce specific pro-inflammatory and degradative OA-related markers (e.g., interleukin IL-6, NF-κB, metalloprotease MMP-13, and cartilage oligomeric matrix protein COMP-2). Both HHA/BC and HHA/BC+PRP similarly prompted scratch repair. Overall, these outcomes provide deeper insights into the biochemical and biological properties of these innovative injectable formulations, highlighting their potential application in OA management.